Aortopathy associated with bicuspid aortic valve: advances in clinical and hemodynamics research - Yang, Minghui; Nie, Zixiong; Yue, Honghua; Liang, Weitao; Wu, Zhong (Frontiers in Physiology, 2025)
Having a bicuspid aortic valve (BAV) is the most common congenital heart disease, affecting 0.5%–2% of the population, with significant heterogeneity in clinical presentation, complications, and outcomes. Hemodynamic disturbances, including wall shear stress (WSS), eccentric flow, helical flow and energy turbulence, are critical in the development and progression of BAV-associated aortopathy, which is characterized by ascending aortic dilation, aortic aneurysm, and dissection. The interplay between genetic factors and hemodynamic abnormalities further complicates disease mechanisms, influencing clinical management and prognosis. To investigate the hemodynamic characteristics of BAV-associated aortic disease before and after surgery, this study reviewed recent advances in the understanding of the hemodynamic and genetic mechanisms underlying BAV-associated aortic disease, as well as clinical treatment strategies and recommendations for managing cases with additional genetic factors. This paper systematically summarizes the changes in hemodynamic parameters related to aortopathy in patients with BAV before and after surgery and their correlation with aortic dilation. This paper also explores the influence of different aortic valve morphotypes and functional phenotypes on hemodynamic parameters. Notably, this review focuses on the unique hemodynamic features of paediatric and young patients with BAVs and reviews clinical management recommendations for this group. The relationship between postoperative hemodynamic changes and clinical outcomes, such as redilation and long-term survival rates, warrants further exploration in BAV patients.